HUBUNGAN ANTARA KONSEP DIRI DENGAN KECENDERUNGAN MENJADI KORBAN BULLYING PADA REMAJA AWAL - Herdyanti, Fidela; Margaretha, M (Jurnal Psikologi, 2016)
The purpose of this research was to determine the relationship between self-concept and tendency to become bully victim in early adolescents. Bullying is an act in which a person or group try to hurt, damage, oppress or do other negative actions to someone who is weak. Bullying occurs repeatedly time to time and will continue to occur if there is someone who feels having power (called as actors) and someone who feels weak (called as victims). Those could happen due to the imbalance in their development of self-concept. This study is a survey research. The subjects were 179 students in Junior High School in Surabaya (67 males and 112 females) with age ranged from 12 to 14 years old. Data were collected using the Self-Concept Questionnaire (20 items) and Bully Victim Questionnaire (16 items). Data were analyzed using Pearson's product moment. The results of this study found a negative correlation between self-concept and the tendency to be bully victim in early adolescence (r= -.772; p< .001). Negative correlation had meaning that adolescents with positive self-concept were less vulnerable to be bully victim, while adolescents with negative self-concept would tend to be bully victim. It is recommended for further research to employ better methods, theories and measuring tools.Â Â